Consciousness : an introduction - Blackmore, Susan (Routledge, 2018)
Now considered the 'last great mystery of science', consciousness was once viewed with extreme scepticism and rejected by mainstream scientists. It is now a significant area of research, albeit a contentious one, as well as a rapidly expanding area of study for students of psychology, philosophy, and neuroscience.